Rare BRAF gene fusions in metastatic early-onset colon cancer: A case report - Tingting Zhao; Junting Yang; Meirong Wang; Jie Liu (Heliyon)
Gene fusions offer new therapeutic options for patients with metastatic colon cancer (CC). BRAF gene fusions are infrequent somatic mutations found in CC with prognostic and promising targeted therapies. CC diagnosed before the age of 50 was regarded as early-onset CC (EOCC). The incidence of EOCC is increasing, yet there is a clear unmet need to improve the management of EOCC. Herein, we selectively reported a case of metastatic EOCC with rare BRAF gene fusions. The right-sided tumors were radically resected. Next-generation sequencing (NGS) was performed on formalin-fixed paraffin-embedded tissues to eliminate gene variations. Histologically, the colonic hepatic flexure showed focal mucinous adenocarcinoma changes along with high-grade intraepithelial neoplasia. The results of histopathological examination belonged to pT1bN1bM0 ⅢA stage. Targeted DNA sequencing revealed AGAP3::BRAF (A10;B9) fusion and BRAF::AGAP3 (B8;A11) fusion were simultaneously detected in this case. Microsatellite instability-high (MSI-H) and RAS/BRAF V600E mutations were not detected. During a limited 1.5-year follow-up period, neither a confirmed local recurrence nor a distant organ metastasis occurred in this case. We propose that BRAF fusion variations can occur in metastatic EOCC.